Implementasi Analisis SWOT dalam Strategi Pemasaran Bisnis Kuliner Ayam Panggang Banjarejo di Madiun - Risalatin Risalatin (ISLAMIC BUSINESS and FINANCE (IBF), 2020)
This study examines the application of SWOT analysis in the Banjarejo grilled chicken restaurant business located in the city of Madiun. The results of this study indicate that the banjarejo grilled chicken restaurant has the courage to compete in a competitive competitive market. The threat from this business is relatively small because in the city of Madiun itself Banjarejo grilled chicken is a well-known culinary. With the marketing strategy of Banjarejo grilled chicken which uses two marketing strategies, namely offline marketing which is carried out by print promotion media and online with social media and in collaboration with go food.